KINERJA LINGKUNGAN, GREEN ACCOUNTING DAN KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Tanjung, Abdul Hafiz; Lestari, Putri (Jurnal Akuntansi Trisakti, 2025)
This study aims to provide empirical evidence on the impact of green accounting classification on financial performance in publicly listed manufacturing companies in Indonesia. Using environmental performance ratings from PROPER, we classify companies into 42 companies with good green accounting and 12 companies with bad green accounting. Next, we selected samples using random sampling technique, then tested the differences in financial performance with ROA, ROE, NPM, EVA proxies from the two groups using independent samples test and Mann-Whitney U test. The results indicate that companies with good green accounting classification have significantly higher financial performance than companies with bad green accounting classification using ROA, NPM and EVA proxies. These findings highlight the importance of environmental responsibility in enhancing corporate financial outcomes, suggesting that firms with poor environmental performance should improve their green accounting practices to strengthen financial sustainability.